Wakaf construction process / Khairul Azhar Khalid - Khalid, Khairul Azhar (2018)
The Johor state government in 1982 established the Yayasan Pelajaran Johor (YPJ) through Enactment No. 8 of 1982 to manage the loan / scholarship requirements for qualified Johor state students to pursuing their education at Higher Education Institutions both local and overseas. The effort to create Yayasan Pelajaran Johor (YPJ) with this objective at this moment is very important as the number of Johorean capable students grows in need of a specialized body to organize their loans and scholarships.